ANALISIS BEBAN KOGNITIF SISWA DALAM PEMANFAATAN MEDIA DIGITAL PADA PEMBELAJARAN INFORMATIKA DI SMP: TINJAUAN TEORI COGNITIVE LOAD - Nuranisa Ramli; Farida Febriati (STKIP Subang, 2026)
This study aims to analyze students’ cognitive load in digital-based informatics learning and identify the influence of digital learning media on students’ motivation and understanding. This study used a qualitative descriptive method with a case study approach. Data were collected through classroom observations and interviews with an informatics teacher. The findings showed that students experienced difficulties in understanding abstract concepts related to artificial intelligence and data quality principles. In addition, students’ attention spans tended to decrease during lecture-dominated learning. However, students showed higher enthusiasm when interactive digital media, educational games, and animated videos were used in the classroom. The findings were analyzed using Cognitive Load Theory, Multimedia Learning Theory, and constructivist learning theory. The study concludes that interactive multimedia and segmented learning content can reduce extraneous cognitive load and improve student engagement in informatics learning. Therefore, the integration of interactive digital media and AI-based animated learning videos is recommended to improve the effectiveness of technology-based learning. Keywords: Cognitive Load, Digital Learning Media, Informatics Learning, Multimedia Learning